Development of a generic interactive model for e-learning contents/tools focused to evaluate learning of the students according to bloom's taxonomy - Saleh, Md. Mynuddin (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.